2020
DOI: 10.1111/phpp.12546
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of high‐dose ultraviolet A‐1 phototherapy for acute exacerbation of atopic dermatitis in Asians

Abstract: Background/PurposeAtopic dermatitis (AD) is an inflammatory skin disease characterized by a chronic course of exacerbations and remissions. High‐dose ultraviolet A‐1 (UVA‐1) phototherapy has been effective in the treatment of acute exacerbations of AD. However, there have been no case studies in Asian patients to date. We investigated the effectiveness of high‐dose UVA‐1 phototherapy for treating acute exacerbation of AD in Asian patients.MethodThis study included 16 patients with acute exacerbation of AD. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Blind bilateral comparisons and randomized controlled studies performed in small populations of AD patients demonstrated high response rates reaching 90%–100%, without a significant difference between high‐dose and medium‐dose UVA1 phototherapy 13,23 . In retrospective studies, response rates to UVA1 phototherapy in AD patients were similar to those reported in this study, regardless of dosages 10–12 . However, in a large retrospective study performed in India, there were low improvement rates of 53% 9 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Blind bilateral comparisons and randomized controlled studies performed in small populations of AD patients demonstrated high response rates reaching 90%–100%, without a significant difference between high‐dose and medium‐dose UVA1 phototherapy 13,23 . In retrospective studies, response rates to UVA1 phototherapy in AD patients were similar to those reported in this study, regardless of dosages 10–12 . However, in a large retrospective study performed in India, there were low improvement rates of 53% 9 .…”
Section: Discussionsupporting
confidence: 80%
“…13,23 In retrospective studies, response rates to UVA1 phototherapy in AD patients were similar to those reported in this study, regardless of dosages. [10][11][12] However, in a large retrospective study performed in India, there were low improvement rates of 53%. 9 The response rates in our patients are in the range of those reported in previous studies and even exceed the response rates of some studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, treatment with ultraviolet (UV) light, i.e. UV phototherapy, is long known to be effective in the treatment of pruritic skin diseases such as psoriasis, atopic dermatitis (AD) and mycosis fungoides (9)(10)(11).…”
mentioning
confidence: 99%